Gender, ritual and social formation in West Papua; A configurational analysis comparing Kamoro and Asmat - Pouwer, Jan (Leiden - Boston Brill, 2010)
This study, based on a lifelong involvement with New Guinea, compares the culture of the Kamoro (18,000 people) with that of their eastern neighbours, the Asmat (40,000), both living on the south coast of West Papua, Indonesia. The comparison, showing substantial differences as well as striking similarities, contributes to a deeper understanding of both cultures. Part I looks at Kamoro society and culture through the window of its ritual cycle, framed by gender. Part II widens the view, offering in a comparative fashion a more detailed analysis of the socio-political and cosmo-mythological setting of the Kamoro and the Asmat rituals. Next is a systematic comparison of the rituals. The comparison includes a cross-cultural, structural analysis of relevant myths. This publication is of interest to scholars and students in Oceanic studies and those drawn to the comparative study of cultures. Jan Pouwer (1924) started his career as a government anthropologist in West New Guinea in the 1950s and 1960s, with periods of intensive fieldwork, in particular among the Kamoro. A distinguished anthropologist, he held professorships at universities around the world.
English
Keywords: Politics & government; indonesia; papua culture; oceanic studies; anthropology; gender studies; Asmat people; Canoe; Headhunting; Kamoro; Kamoro language; Sago